Sensitivity of Twentieth-Century Sahel Rainfall to Sulfate Aerosol and CO2 Forcing - Ackerley, D; Booth, B; Knight, S; Highwood, E; Frame, D; Allen, MR; Rowell, D (2011)
Afull understanding of the causes of the severe drought seen in the Sahel in the latter part of the twentiethcentury remains elusive some 25 yr after the height of the event. Previous studies have suggested that this drying trend may be explained by either decadal modes of natural variability or by human-driven emissions (primarily aerosols), but these studies lacked a sufficiently large number of models to attribute one cause over the other. In this paper, signatures of both aerosol and greenhouse gas changes on Sahel rainfall are illustrated. These idealized responses are used to interpret the results of historical Sahel rainfall changes from two very large ensembles of fully coupled climate models, which both sample uncertainties arising from internal variability and model formulation. The sizes of these ensembles enable the relative role of human-driven changes and natural variability on historic Sahel rainfall to be assessed. The paper demonstrates that historic aerosol changes are likely to explain most of the underlying 1940-80 drying signal and a notable proportion of the more pronounced 1950-80 drying. © 2011 American Meteorological Society.